Impacts of climate on the biodiversity-productivity relationship in natural forests. Issue 1 (December 2018) - Fei, Songlin; Jo, Insu; Guo, Qinfeng; Wardle, David; Fang, Jingyun; Chen, Anping; Oswalt, Christopher; Brockerhoff, Eckehard
Abstract Understanding biodiversity-productivity relationships (BPRs) is of theoretical importance, and has important management implications. Most work on BPRs has focused on simple and/or experimentally assembled communities, and it is unclear how these observed BPRs can be extended to complex natural forest ecosystems. Using data from over 115, 000 forest plots across the contiguous United States, we show that the bivariate BPRs are positive in dry climates and hump-shaped in mesic climates. When considering other site characteristics, BPRs change to neutral in dry climates and remain hump-shaped in humid sites. Our results indicate that climatic variation is an underlying determinant of contrasting BPRs observed across a large spatial extent, while both biotic factors (e.g., stand age and density) and abiotic factors (e.g., soil properties) can impact BPRs within a given climate unit. These findings suggest that tradeoffs need be made when considering whether to maximize productivity vs. conserve biodiversity, especially in mesic climates. There has been recent interest in understanding why the biodiversity-productivity relationship varies among studies and across scales. Here Fei et al. show that climatic variation drives forest biodiversity-productivity relationships at large spatial scales, whilst biotic and abiotic factors are important in given climate units.